Peningkatan Kualitas UMKM Wonorejo Madiun Sebagai Dasar Pengembangan Wisata Budaya - Mardianto, M. Fariz Fadillah; Amelia, Dita; Pusporani, Elly; Rani, Lina Nugraha; Siregar, Naufal Ramadhan Al Akhwal; Nurrohmah, Zidni ‘Ilmatun; Previan, Anggara Teguh; Putri, Ferdiana Friska Rahmana (LPPM Universitas Trunojoyo Madura, 2024)
Wonorejo Village is one of the villages in Madiun Regency which has natural and cultural potential that can be integrated into local economic development through MSMEs and the tourism sector. MSME empowerment activities provide opportunities for local communities to create jobs and achieve Sustainable Development Goals (SDGs) in maintaining economic stability. By focusing on improving the quality of MSMEs and through appropriate mentoring activities, this village can achieve inclusive and sustainable economic development. This activity aims to provide counseling and assistance regarding digitalization of MSME marketing integrated with the potential of Wonorejo Village as a tourist village for Wonorejo Temple tourism. The method of community service consists of several stages. First, provide assistance regarding product design and marketing aspects. Second, regarding training in digitalizing MSMEs from creating social media for MSME products. Third, in the form of training in obtaining permits, business legality and halal certification. Fourth, in the form of mentoring and evaluation activities during the mentoring and training process. The results of this community service, namely counseling and assistance to MSMEs in Wonorejo Village, have a positive effect on increasing the products of MSMEs in Wonorejo Village. Recommendations and sustainability that can be given are increasing the role of the Wonorejo Village community in developing tourism because of the resources and quality of the village's MSMEs so that they are able to encourage success as a tourist village from the community service activities that have been carried out.